(untitled) (Revista Investigación & praxis en CS Sociales, 2023)
This article summarizes qualitative research focused on analyzing pedagogical strategies in virtual environments during the pandemic at the Guillermo Cote Bautista Educational Institution. It highlights its relevance by providing new perspectives and improving pedagogical practices, effectively adapting to virtual educational scenarios, and providing valuable guidance for other institutions. The assessment of the impact on learning highlights how these strategies positively influenced the development of skills and the achievement of educational objectives in a virtual environment.